2008
DOI: 10.1016/j.dnarep.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which herpes simplex virus DNA polymerase limits translesion synthesis through abasic sites

Abstract: Results suggest a high probability that abasic (AP) sites occur at least once per herpes simplex virus type 1 (HSV-1) genome. The parameters that control the ability of HSV-1 DNA polymerase (pol) to engage in AP translesion synthesis (TLS) were examined because AP lesions could influence the completion and fidelity of viral DNA synthesis. Pre-steady-state kinetic experiments demonstrated that wild-type (WT) and exonuclease-deficient (exo -) pol could incorporate opposite an AP lesion, but full TLS required abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…The bypass of abasic sites by replicative DNA polymerases is very low, depending on the sequence context and counteracted by the proofreading activity (12,13,40,41). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bypass of abasic sites by replicative DNA polymerases is very low, depending on the sequence context and counteracted by the proofreading activity (12,13,40,41). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unrepaired abasic sites are highly blocking lesions for replicative DNA polymerases (10), although mutant polymerases with impaired proofreading activity or with mutations in the polymerization active site residues that affect the incoming nucleotide selection have been shown to have enhanced AP site bypass capacity (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…These may arise through spontaneous base loss and as a result of DNA glycosylase action, presumably that of the virus-encoded UL2. Because AP sites are noninstructional and cause UL30 to stall (10), their occurrence in the viral genome necessitates that they are repaired by BER. Here, we have shown that UL30, a replicative B family Pol and a Pol from the herpesviridae family, possesses both AP and 5Ј dRP lyase activities that are integral to BER.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HSV-1, a recent study showed that DNA isolated from HSV-1-infected cultured fibroblasts contains a steady state of 2.8-5.9 AP sites per viral genome equivalent (10). Because AP sites are noninstructional lesions, they may either induce mutagenesis or cause replisome stalling.…”
mentioning
confidence: 99%
See 1 more Smart Citation